The new semantics suggested for the marketing mix by millennials - Zafar, A. (Blue Eyes Intelligence Engineering and Sciences Publication, 2019)
This is an auxiliary study dealing with the 4 Ps of the Marketing Mix Model introduced by Robert F. Lauterborn. It focused on the comparative popularity of the components of the Marketing Mix among the contemporary consumers of fast moving consumer goods (FMCGs) produced by Unilever and Proctor and Gamble in the capital city of Islamabad, Pakistan. These two companies are two of the prominent multi-national companies providing products of day-to-day use in the country. This study sought to find out the most popular vocabulary to describe the components of the Marketing Mix among the consumers of FMCGs who are marketing graduates and thereby, revise, enhance and refurbish it to make it more relevant to the millennial perspective. The perspective of the consumers is important to gauge if the Lauterborn’s Model is still applicable to the modern consumers or if the consumers have other marketing priorities, which may differ from the model. Data were collected through a survey based on the random sampling technique from millennial consumers at five local universities in the city. Analysis of the data revealed useful information regarding the validity of the semantics in the presently accepted marketing mix. Findings of this study have the potential to assist marketing strategies, especially at the advertising departments of the leading FMCG chains Unilever and Proctor and Gamble. Results of this study may also be applied to marketing campaigns of similar prominent multi-national companies producing FMCGs in Pakistan, like Nestle, Reckitt Benckiser and the Coca Cola Company.